A nomenclatural review of family-group names in the Tettigoniidae (Orthoptera: Ensifera) - Connors, Matthew G (Zootaxa, 2024)
The Tettigoniidae is the largest and most complex family within the Orthoptera, and perhaps expectedly, its systematic arrangement is largely unsatisfactory. Recent phylogenetic studies within the group have been almost wholly at odds with traditional morphological classification, and it is clear that a great number of changes will be made to the family in the near future. To remove the element of nomenclatural uncertainty that will inevitably arise with such dramatic changes, I here provide a complete annotated list of all family-group names proposed within the Tettigoniidae in explicit order of priority. I provide details of the authorship, availability, current validity, current rank(s) and name(s), type genus, stem, and parent taxon of each of the 182 proposed family-group names, of which 171 represent available names. I also make several nomenclatural changes, the most significant of which is the replacement of available but informal groupings (e.g. species groups) with formal tribes, subtribes, and infratribes. Other major changes are the replacement of Nedubini syn. nov. with Apteropedetini stat. nov., the replacement of Eumegalodontina (unavailable name) with Lesinina stat. nov., and the designation of Acanthodidae as nomen oblitum with respect to Pleminiae (nomen protectum). To reduce confusion in future, I recommend that all new family-group names be clearly proposed as new, with a correct rank, stem, suffix, and diagnosis, that informal groupings are explicitly proposed as informal, and that formal names are used and proposed in place of informal names wherever possible. I additionally propose that the suffixes -iti and -ita be used for all supertribe and infratribe rankings within the Tettigoniidae. Finally, I discuss the various names that have been used for taxa between the ranks of family and subfamily, with the recommendation that informal 'group' and 'clade' names with unambiguous suffixes are formed from available subfamily names.